answersLogoWhite

0

If you mean y = Sin(pi(x))

Then

Use the chain rule

dy/dx = dy/du X du/dx

Let

pi(x) = u

y = Sin (u)

dy/du = Cos(u)

u = pi(x)

du/dx = pi

Combining

dy/dx = pi Cos(u) = piCos (pi(x)). The answer!!!!!

User Avatar

lenpollock

Lvl 16
1w ago

Still curious? Ask our experts.

Chat with our AI personalities

ProfessorProfessor
I will give you the most educated answer.
Chat with Professor
EzraEzra
Faith is not about having all the answers, but learning to ask the right questions.
Chat with Ezra
JudyJudy
Simplicity is my specialty.
Chat with Judy
More answers

pi cos(pi x)

User Avatar

Wiki User

16y ago
User Avatar

Add your answer:

Earn +20 pts
Q: What is the derivative of sin pi x?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Trigonometry

How do you determine the sign of a sine curve?

For 0 < x < pi. sin(x) is positive,for pi < x < 2*pi, sin(x) is negative and these intervals can be left or right-shifted by any multiple of 2*pi radians.


Derivative of sin2 (x)?

d/dx (sin x)^2=2sinxcosx


When does cotangent equal -1?

cot[x]= -1 cot[x] = cos[x] / sin[x] cos[x] / sin[x] = -1 cos[x] = -sin[x] |cos[x]| = |sin[x]| at every multiple of Pi/4 + Pi/2. However, the signs disagree at 3Pi/4 + nPi, where n is an integer.


Sin x divided by 1 minus cos x equals csc plus cot x?

It helps to convert this kind of equation into one that has only sines and cosines, by using the basic definitions of the other functions in terms of sines and cosines. sin x / (1 - cos x) = csc x + cot x sin x / (1 - cos x) = 1 / sin x + cos x / sin x Now it should be easy to do some simplifications: sin x / (1 - cos x) = (1 + cos x) / sin x Multiply both sides by 1 + cos x: sin x (1 + cos) / ((1 - cos x)(1 + cos x)) = (1 + cos x)2 / sin x sin x (1 + cos) / (1 - cos2x) = (1 + cos x)2 / sin x sin x (1 + cos) / sin2x = (1 + cos x)2 / sin x sin x (1 + cos x) / sin x = (1 + cos x)2 1 + cos x = (1 + cos x)2 1 = 1 + cos x cos x = 0 So, cos x can be pi/2, 3 pi / 2, etc. In some of the simplifications, I divided by a factor that might be equal to zero; this has to be considered separately. For example, what if sin x = 0? Check whether this is a solution to the original equation.


How do you express cosine in terms of cotangent?

cos(x)=sin(x-tau/4) tan(x)=sin(x)/cos(x) sin(x)=tan(x)*cos(x) cos(x)=tan(x-tau/4)*cos(x-tau/4) you can see that we have some circular reasoning going on, so the best we can do is express it as a combination of sines and cotangents: cos(x)=1/cot(x-tau/4)*sin(x-tau/2) tau=2*pi